2015
DOI: 10.17576/jem-2015-4902-07
|View full text |Cite
|
Sign up to set email alerts
|

Are Profit Sharing Rates in Mudharabah Account Linked to Interest Rates? An Investigation on Islamic Banks in GCC Countries

Abstract: In principle, Islamic banking prohibits interest and advocates profit and loss sharing in its operations

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 25 publications
0
2
0
1
Order By: Relevance
“…Namun, dari ketiga jenis kerja sama ini mereka memiliki konsep sipallambi melakukannya karena maksud membantu yang lainnya baik dari sisi tenaga maupun dari sisi materi (Vel & Bedner, 2015 Mentode adalah bentuk kerja sama antara pemilik dan petani penggarap dengan menghitung berapa luas lahan yang diselesaikan. Dalam hal ini mereka yang memiliki lahan saling bergantian membantu mengerjakan lahan pertanian dengan tujuan pengeloaan lahan pertanian lebih efisien (Alfian, 2013;D'Antoni & Mishra, 2013;Mulawarman & Kamayanti, 2018;Soonthornchai, 2017;Vel & Bedner, 2015;Suryanto, 2015;Yusof et al, 2015).…”
Section: Koleksi Data Seleksi Kodingunclassified
“…Namun, dari ketiga jenis kerja sama ini mereka memiliki konsep sipallambi melakukannya karena maksud membantu yang lainnya baik dari sisi tenaga maupun dari sisi materi (Vel & Bedner, 2015 Mentode adalah bentuk kerja sama antara pemilik dan petani penggarap dengan menghitung berapa luas lahan yang diselesaikan. Dalam hal ini mereka yang memiliki lahan saling bergantian membantu mengerjakan lahan pertanian dengan tujuan pengeloaan lahan pertanian lebih efisien (Alfian, 2013;D'Antoni & Mishra, 2013;Mulawarman & Kamayanti, 2018;Soonthornchai, 2017;Vel & Bedner, 2015;Suryanto, 2015;Yusof et al, 2015).…”
Section: Koleksi Data Seleksi Kodingunclassified
“…Different findings are presented by Yusof et al (2015) and Yuksel (2017). Yusof et al (2015) found no relationship that prevails between PLS rates and interest rates in the long run.…”
Section: Implementation Of Pls Transactionsmentioning
confidence: 74%
“…Previous studies have tested more on the correlation of interest rate with Islamic banks' return rate. However, previous studies, such as those conducted by Chong and Liu (2009), Yusof et al (2015), Hamza (2016) and Yuksel (2017), are limited to investment account holders (IAH) products. We found Khalidin and Masbar (2017) and Šeho et al (2020) to be the only studies investigating whether IBFRR is interest-free.…”
Section: Introductionmentioning
confidence: 99%
“…However, some previous empirical studies found opposite results whereby IDRs are not linked to conventional interest rates. Yusof et al (2015) assessed the relationship between IDRs and CDRs in the Gulf Cooperation Council (GCC) countries. They found that there is no relationship between IDRs and CDRs in the long run.…”
Section: Review Of Literature Islamic and Conventional Deposit Ratesmentioning
confidence: 99%